PSYCHOLOGICAL METHODS OF PREVENTING VIOLENCE IN SCHOOLS (Conference Zone, 2021)
The article describes the psychological methods of preventing violence in schools and the preventive measures of practicing psychologists. It is also explained that the basis of radical reforms in our country today is the fight against violence.